Peculiarities of Analytical Characteristics of Pectins Extracted from Sunflower Hearts - Sobol, Irina Valeryevna (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: To present the results of the research of the analytical characteristics of pectins extracted from sunflower hearts. Materials and Methods: The object of the research is sunflower grades produced in Southern Russia. The research involved standard and modern methods of the physicochemical analysis. Results: The results showed that this raw material can be considered, first of all, as the future pectin industrial source. High pectin concentration in sunflower hearts proved the raw material technological importance for industrial processing. To assess pectin quality, the following analytical characteristics have been determined – polygalacturonic acid content, acetyl and methoxy components, extent of esterification, and complexing ability. Conclusion: High complexing ability of the sunflower pectin and high content of the polygalacturonic component provide for its possible use in the special and healthy food production. For that, sunflower heart pectins are low-esterified. It means that it is practical to use them as detoxicants.